Spiritual formation of adolescents – a semiotic analysis - Hoffman, L; Janse van Rensburg, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
How do adolescents describe their own spiritual journey? Can people involved in the spiritual formation of adolescents glean helpful information from adolescents’ descriptions? Fifteen semi-structured interviews were conducted with five grade 10 learners from Bloemfontein, South Africa. Through semiotic analysis, the following syntagms were found: family, spiritual leader, knowledge, community, school, speech act and friends. These syntagms fitted into three paradigms: process, role players and content. A semiotic square was constructed for the term “process”. Habermas’s theory of communicative action can be applied to these findings. The study suggests important communicative principles to be utilized in the spiritual formation of adolescents. Limitations and suggestions for further research are also pointed out.